Machine Effective Analysis Using OEE and Six Big Losses Methods in the Filter Making Factory - Avichena , Muhammad Haris Indra; Pudji W., Endang (Nusantara Science and Technology Proceedings)
Improper machine maintenance and handling can cause a decrease in the level of engine performance which results in reduced engine effectiveness and productivity. Filter making company is a company engaged in manufacturing filters. The problem faced by the filter manufacturing company is that the company has a breakdown time on the production machine that is too high which causes the machine performance to decrease. To increase productivity, Total Productive Maintenance (TPM) measurements are calculated using Overal Equipment Effectiveness (OEE) calculations. OEE is a systematic method for measuring the effectiveness of a machine or equipment process. In general, the size of the OEE is influenced by the dominant factor that causes the low performance of a machine or equipment which is commonly called six big losses. After that, get the cause of the problem that occurs by using a causal diagram. The results showed that the OEE value on the production machine was 40.63%, the effectiveness value was classified as low because the OEE value standard for world-class companies was 85%. The biggest factor influencing the low value of OEE on this production machine is performance efficiency with the largest percentage of six big losses found in reduced speed losses and idling and minor stoppages losses with an average percentage of 59.41% and 48.86% of all losses. The thing done to overcome the low OEE value on the production machine is the implementation of autonomous maintenance that is given to each operator, conduct training for operators and maintenance technicians, supervise operators about work hygiene.